In vitro antiplasmodial activity of an optimised series of alkylated (bis)urea and (bis)thiourea polyamine analogs - Birkholtz, Lyn-Marie (University of Pretoria, 2014)
Dissertation (MSc)--University of Pretoria, 2013.